The COVID-19 pandemic and the need for an integrated and equitable approach: an international expert consensus paper - Gerotziafas, Grigoris T.; Catalano, Mariella; Theodorou, Yiannis; Dreden, Patrick Van; Marechal, Vincent; Spyropoulos, Alex C.; Carter, Charles; Jabeen, Nusrat; Harenberg, Job; Elalamy, Ismail; Falanga, Anna; Fareed, Jawed; et al. (Thrombosis and haemostasis, 2021)
Background One year after the declaration of the coronavirus disease 2019 (COVID-19) pandemic by the World Health Organization (WHO) and despite the implementation of mandatory physical barriers and social distancing, humanity remains challenged by a long-lasting and devastating public health crisis. Management Non-pharmacological interventions (NPIs) are efficient mitigation strategies. The success of these NPIs is dependent on the approval and commitment of the population. The launch of a mass vaccination program in many countries in late December 2020 with mRNA vaccines, adenovirus-based vaccines, and inactivated virus vaccines has generated hope for the end of the pandemic. Current Issues The continuous appearance of new pathogenic viral strains and the ability of vaccines to prevent infection and transmission raise important concerns as we try to achieve community immunity against severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) and its variants. The need of a second and even third generation of vaccines has already been acknowledged by the WHO and governments. Perspectives There is a critical and urgent need for a balanced and integrated strategy for the management of the COVID-19 outbreaks organized on three axes: (1) Prevention of the SARS-CoV-2 infection, (2) Detection and early diagnosis of patients at risk of disease worsening, and (3) Anticipation of medical care (PDA). Conclusion The “PDA strategy” integrated into state policy for the support and expansion of health systems and introduction of digital organizations (i.e., telemedicine, e-Health, artificial intelligence, and machine-learning technology) is of major importance for the preservation of citizens' health and life world-wide.
Scientific Reviewer Committee: Grigoris T. Gerotziafas, Mariella Catalano, Yiannis Theodorou, Patrick Van Dreden, Vincent Marechal, Alex C. Spyropoulos, Charles Carter, Nusrat Jabeen, Job Harenberg, Ismail Elalamy, Anna Falanga, Jawed Fareed, Petros Agathaggelou, Darko Antic, Pier Luigi Antignani, Manuel Monreal Bosch, Benjamin Brenner, Vladimir Chekhonin, Mary-Paula Colgan, Meletios-Athanasios Dimopoulos, Jim Douketis, Essam Abo Elnazar, Katalin Farkas, Bahare Fazeli, Gerry Fowkes, Yongquan Gu, Joseph Gligorov, Mark A. Ligocki, Tishya Indran, Meganathan Kannan, Bulent Kantarcioglu, Abdoul Aziz Kasse, Kostantinos Konstantinidis, Fabio Leivano, Joseph Lewis, Alexander Makatsariya, P. Massamba Mbaye, Isabelle Mahé, Irina Panovska-Stavridis, Dan-Mircea Olinic, Chryssa Papageorgiou, Zsolt Pecsvarady, Sergio Pillon, Eduardo Ramacciotti, Hikmat Abdel-Razeq, Michele Sabbah, Mouna Sassi, Gerit Schernthaner, Fakiha Siddiqui, Jin Shiomura, Anny Slama-Schwok, Jean Claude Wautrecht, Alfonso Tafur, Ali Taher, Peter Klein-Wegel, Zenguo Zhai, Tazi Mezalek Zoubida
Gesehen am 03.11.2021